Perspectives： Gene expression in fisheries management - Nielsen, Jennifer L.; Pavey, Scott A. (Current zoology, 2010)
Functional genes and gene expression have been connected to physiological traits linked to effective production and broodstock selection in aquaculture, selective implications of commercial fish harvest, and adaptive changes reflected in non-commercial fish populations subject to human disturbance and climate change. Gene mapping using single nucleotide polymorphisms （SNPs） to identify functional genes, gene expression （analogue microarrays and real-time PCR）, and digital sequencing technologies looking at RNA transcripts present new concepts and opportunities in support of effective and sustainable fisheries. Genomic tools have been rapidly growing in aquaculture research addressing aspects of fish health, toxicology, and early development. Genomic technologies linking effects in functional genes involved in growth, maturation and life history development have been tied to selection resulting from harvest practices. Incorporating new and ever-increasing knowledge of fish gehomes is opening a different perspective on local adaptation that will prove invaluable in wild fish conservation and management. Conservation of fish stocks is rapidly incorporating research on critical adaptive responses directed at the effects of human dis- turbance and climate change through gene expression studies. Genomic studies of fish populations can be generally grouped into three broad categories： l） evolutionary genomics and biodiversity; 2） adaptive physiological responses to a changing environment; and 3） adaptive behavioral genomics and life history diversity. We review current genomic research in fisheries focusing on those that use microarrays to explore differences in gene expression among phenotypes and within or across populations, information that is critically important to the conservation of fish and their relationship to humans [Current Zoology 56 （1）： 157-174, 2010].